An innovative anticonvulsant - a GABAA receptor modulator with an alternative mechanism of action and enzyme-inducing detoxifying properties. (13th April 2021) - Shushpanova, T.; Bokhan, N.; Stankevich, K.; Novozheeva, T.; Shushpanova, O.; Udut, V.; Garganeeva, N.; Markova, E.; Knyazeva, E.; Safronov, S.; Boev, R.; Solonskii, A.
Abstract : Introduction: The development of original drugs - new generation GABAA receptor modulators (GABAAR), with an anti-alcohol orientation, non-addictive and stimulating detoxification processes, makes it possible to increase the effectiveness of therapy and reduce the cost of treatment. Objectives: Study the mechanism of interaction between m-Cl-BHU and GABAA - receptor Methods: Molecular docking was performed to study the molecular docking of m-Cl-BHU with at the binding site of the target protein GABAAR.Radioreceptor studies were carried out using [3H] flunitrazepam binding with synaptosomal receptors in the cerebral cortex of Wistar rats in experimental alcoholism under the influence of therapy with m-CL-BHU. Kinetic parameters (T1/2, Clt, MRT, MET, AUC) of a model substrate - antipyrine were determined in the saliva of healthy volunteers and alcoholic patients. Results: IResults of molecular docking (Schrödinger program (Glide) showed: m-CL-BHU (meta-chlorobenzhydryl urea) is complementary to the benzodiazepine GABAAR. Binding energy is low) (scoring (GScore) -11.14 kKal/mol); m-CL-BHU interacts with key amino acids at the α1γ2 interface: Tyr159, Tyr209, H101 Phe77 and is characterized by a high degree of model fit - dG insert: 0.741 Binding of [3H] flunitrazepam to the benzodiazepine site of GABAAR in rat brain in experimental alcoholism, who received 14 days of m-CL-BHU at 100 mg/kg /day, increased in receptor affinity. Changes in the kinetic parameters (T1/2, Clt, MRT, MET, AUC) of a model substrate - antipyrine in the saliva of healthy volunteers and alcoholic patients using Galodif (m-CL-BHU) at 300 mg/day 21 days Conclusions: m-CL-BHU - GABAA receptor modulator with an alternative mechanism of action Disclosure: No significant relationships.